Viruses Without Borders: Global Analysis of the Population Structure, Haplotype Distribution, and Evolutionary Pattern of Iris Yellow Spot Orthotospovirus (Family Tospoviridae, Genus Orthotospovirus) - Tabassum, Afsha; Ramesh, S. V.; Zhai, Ying; Iftikhar, Romana; Olaya, Cristian; Pappu, Hanu R. (Frontiers in Microbiology, 2021)
Iris yellow spot, caused by Iris yellow spot orthotospovirus (IYSV) (Genus: Orthotospovirus, Family: Tospoviridae), is an important disease of Allium spp. The complete N gene sequences of 142 IYSV isolates of curated sequence data from GenBank were used to determine the genetic diversity and evolutionary pattern. In silico restriction fragment length polymorphism (RFLP) analysis, codon-based maximum likelihood studies, genetic differentiation and gene flow within the populations of IYSV genotypes were investigated. Bayesian phylogenetic analysis was carried out to estimate the evolutionary rate. In silico RFLP analysis of N gene sequences categorized IYSV isolates into two major genotypes viz., IYSV Netherlands (IYSVNL; 55.63%), IYSV Brazil (IYSVBR; 38.73%) and the rest fell in neither group [IYSV other (IYSVother; 5.63%)]. Phylogenetic tree largely corroborated the results of RFLP analysis and the IYSV genotypes clustered into IYSVNL and IYSVBR genotypes. Genetic diversity test revealed IYSVother to be more diverse than IYSVNL and IYSVBR. IYSVNL and IYSVBR genotypes are under purifying selection and population expansion, whereas IYSVother showed decreasing population size and hence appear to be under balancing selection. IYSVBR is least differentiated from IYSVother compared to IYSVNL genotype based on nucleotide diversity. Three putative recombinant events were found in the N gene of IYSV isolates based on RDP analysis, however RAT substantiated two among them. The marginal likelihood mean substitution rate was 5.08×10-5 subs/site/year and 95% highest posterior density (HPD) substitution rate between 5.11×10-5–5.06×10-5. Findings suggest that IYSV continues to evolve using population expansion strategies. The substitution rates identified are similar to other plant RNA viruses.